1983
DOI: 10.1152/ajpendo.1983.244.6.e560
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine stimulates somatostatin release from perifused hypothalamic cells

Abstract: We studied the release of immunoreactive somatostatin (IR-SRIF) from hypothalamic cells that were obtained from rats and dispersed with the aid of collagenase. Twenty-four hours after dispersion, cells were placed in a column supported by a matrix of preswollen Biogel P2 and perifused. Fractions were collected on ice and subsequently assayed for SRIF. SRIF release was stimulated markedly by potassium depolarization (KCl, 56 mM), by the Na+-K+-ATPase inhibitor ouabain (10(-4) M), and by dopamine at concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
1

Year Published

1985
1985
1997
1997

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
0
8
1
Order By: Relevance
“…Although influences of DA at other brain levels or on hypothalamic GRF cannot be ruled out, results of the lesioning experiment in the pres ent study suggest that DA stimulates GH secretion by in hibiting the release and/or synthesis of somatostatin-like GH release-inhibitory factor located in the preoptic area of the goldfish brain. These results in goldfish are in contrast to observations in the rat where DA has been shown to stimulate in vivo somatostatin release into hypophyseal portal blood [10] and from perifused hypothalamic cells in vitro [41], Further studies concerning the relationship of DA to hypothalamic somatostatin content and release are currently being conducted in our laboratory.…”
Section: Discussioncontrasting
confidence: 86%
“…Although influences of DA at other brain levels or on hypothalamic GRF cannot be ruled out, results of the lesioning experiment in the pres ent study suggest that DA stimulates GH secretion by in hibiting the release and/or synthesis of somatostatin-like GH release-inhibitory factor located in the preoptic area of the goldfish brain. These results in goldfish are in contrast to observations in the rat where DA has been shown to stimulate in vivo somatostatin release into hypophyseal portal blood [10] and from perifused hypothalamic cells in vitro [41], Further studies concerning the relationship of DA to hypothalamic somatostatin content and release are currently being conducted in our laboratory.…”
Section: Discussioncontrasting
confidence: 86%
“…4). , 1980;Richardson et al 1983), but a dose-re¬ sponse curve has never previously been established.…”
Section: Resultsmentioning
confidence: 99%
“…This experiment is representative of three others. For details, see Materials and Methods. lates hypothalamic SS release in both in vivo (Junier et al, 1983) and in vitro (Richardson et al, 1983) systems. Robbins (1985) also demonstrated that DA increases SS release from cerebral cortical cells in culture.…”
Section: Discussionmentioning
confidence: 97%